2020
DOI: 10.1038/s41467-020-16232-6
|View full text |Cite
|
Sign up to set email alerts
|

The native ORAI channel trio underlies the diversity of Ca2+ signaling events

Abstract: The essential role of ORAI1 channels in receptor-evoked Ca 2+ signaling is well understood, yet little is known about the physiological activation of the ORAI channel trio natively expressed in all cells. The roles of ORAI2 and ORAI3 have remained obscure. We show that ORAI2 and ORAI3 channels play a critical role in mediating the regenerative Ca 2+ oscillations induced by physiological receptor activation, yet ORAI1 is dispensable in generation of oscillations. We reveal that ORAI2 and ORAI3 channels multimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
149
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(172 citation statements)
references
References 54 publications
23
149
0
Order By: Relevance
“…3A, B ). In agreement with previous data from our lab 28 , we showed that under conditions of stimulation with low concentrations of CCh (10 µM), relieving the negative regulatory effects of Orai2 and Orai3 on native Orai1 results in enhanced percentage (∼70%) of Orai2,3-KO cells responding with Ca 2+ plateaus ( Fig. 3C, Q-S; compare to 16% of WT-HEK293 cells in Fig.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…3A, B ). In agreement with previous data from our lab 28 , we showed that under conditions of stimulation with low concentrations of CCh (10 µM), relieving the negative regulatory effects of Orai2 and Orai3 on native Orai1 results in enhanced percentage (∼70%) of Orai2,3-KO cells responding with Ca 2+ plateaus ( Fig. 3C, Q-S; compare to 16% of WT-HEK293 cells in Fig.…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, Orai-TKO cells have a significantly reduced frequency of oscillations with only ∼3 oscillations/14 min ( Fig. 1H-I see also 28 ). These findings suggest that STIM proteins provide an additional control mechanism over the rate of ER Ca 2+ release through IP 3 Rs.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations